Scene Graph For Dynamic Virtual Environment: Spangraph - Kim, Hyun Suk; Ko, Heedong; Lee, Kunwoo; Kim, Lae Hyun; Ahn, Jaehong; Park, Kyoung Dong (International Journal of Virtual Reality, 2000)
The VRML (Virtual Reality Modeling Language) file format is a popular file format for describing a graphical scene: object shapes, appearance properties, animation, and interactions. However, the format does not provide any mechanism for describing the order of objects’ appearances or their changes over time. Instead, an interface to Java is offered for controlling the temporal relationships between objects in the scene. The use of Java makes it difficult for a person with his programming skill to author a dynamic virtual environment. In this paper we attach a span and an age to each object and their hierarchical and temporal relations are expressed in a new data structure, called a span graph (SpanGraph). An object in the span graph, when alive, grows its age and performs associated actions according to its age during the extent of the time span. Furthermore, the object may have child objects whose spans are sub-extents of the parent span. In this paper, we demonstrate uses of the SpanGraph in virtual studio and virtual engineering design applications.